Haskins Society Journal. studies in medieval history - Morillo, Stephen; Korngiebel, Diane M. (Diane Marie) (Boydell Press, 2006)
This latest volume of the Haskins Society Journal presents recent research on the Anglo-Saxon, Anglo-Norman, Viking and Angevin worlds of the eleventh and twelfth centuries; topics range from a major reassessment of King Alfred [the last work finished by.